Tanfīż aṭ-Ṭarīqah (Buzz Group) lī at-Tarqiyyat Natāʾij at-Taʿallum lī aṭ-Ṭullāb fī Māddah al-Lugah al-ʿArabiyyah bī al-Madrasah aṡ-Ṡānawiyyah al-Ḥukūmiyyah: Application of Buzz Group Learning Method to Improve Learning Outcomes in Arabic Language Subjects at MTsN 3 Ngawi - Siti Maharani Hasibuan; Agus Yasin; Azhar Amir Zaen; Sri Wahyuni Utamy (Jurusan Pendidikan Bahasa Arab UIN Sunan Kalijaga, 2024)
Madrasah Tsanawiyah Negeri (MTsN) 3 Ngawi is a public madrasah that implements Arabic language learning for students using Arabic language textbooks from the Ministry of Religious Affairs (KEMENAG). However, there are several issues during the learning process in the teaching and learning program. The teacher still uses the lecture and translation methods, which cause students to become easily bored and less attentive to the teacher's explanations, making the learning process less than optimal and resulting in minimal student learning outcomes. In this study, the researcher used Classroom Action Research (CAR) with four stages: planning, action, observation, and reflection. Therefore, the researcher seeks to solve these issues by implementing the